2016
DOI: 10.21608/ejabf.2016.11181
|View full text |Cite
|
Sign up to set email alerts
|

Study of some Alluvial soil's sediments characteristics in Toshka Depression, Egypt.

Abstract: Egypt is one of the most populous countries in Africa and the Middle East. Toshka Depression (TD), are located to the west of Lake Nasser, in the western desert of Egypt they consist of four deep-cut basins connected by naturally and far away about 250 km south of Aswan. Alluvium Operation is estimated that on the average of 133.54 million tons enter the high dam reservoir each year. About 97 % of this amount precipitates in the reservoir and 3% is carried through Aswan High dam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, soils of Toshka were studied by different land evaluation systems such as Storie index, ASLE program, MicroLEIS (Abd El-Aziz, 2018 andSalah, 2018)). These studies were showed that most common limitation factors for crop production in Toshka area are the shallow soil depth, highcontent of gravel, soil texture, low soil fertility and soil pH (Abbas et al, 2010;Fayed et al, 2010;Sherif, 2016;Aldabaa et al, 2018;Salah, 2018 andMohamed et al, 2019). However, the conventional assessment of land suitability is based on evaluating the sampled sites without taking in consideration the unsampled ones.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, soils of Toshka were studied by different land evaluation systems such as Storie index, ASLE program, MicroLEIS (Abd El-Aziz, 2018 andSalah, 2018)). These studies were showed that most common limitation factors for crop production in Toshka area are the shallow soil depth, highcontent of gravel, soil texture, low soil fertility and soil pH (Abbas et al, 2010;Fayed et al, 2010;Sherif, 2016;Aldabaa et al, 2018;Salah, 2018 andMohamed et al, 2019). However, the conventional assessment of land suitability is based on evaluating the sampled sites without taking in consideration the unsampled ones.…”
Section: Introductionmentioning
confidence: 99%
“…It reaches its annual maximum in the north, reaching 42%, and decreasing with the direction to the south, to record 24%. Figure (6).…”
Section: Relative Humiditymentioning
confidence: 99%
“…However, calcium carbonate presence vertically rarely affect the movement of water, but may prevent the roots movement and spread. According to FAO Calcium Carbonate Index (Sideruis, 1984 andFAO,1985) to give relative weights to each category; This factor's values were divided into five different categories and reclassified, as shown in the table (6) and figure (9). Gypsum is agricultural useful; It improves the state of soil construction, as a source of calcium, plant's nutrient and replaces mutual sodium in soils, so, it prevent soil degradation.…”
Section: Salinity (Ec)mentioning
confidence: 99%